2013
DOI: 10.3177/jnsv.59.144
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum OLL2712 Regulates Glucose Metabolism in C57BL/6 Mice Fed a High-Fat Diet

Abstract: SummaryThe aim of the present study was to determine the effect of oral administration of Lactobacillus plantarum OLL2712 (L. plantarum OLL2712) on glucose and lipid metabolism in mice with high-fat diet-induced obesity. Mice that had been administered 10 9 cfu heatkilled L. plantarum OLL2712 for 12 wk showed significant reduction of blood glucose levels in response to insulin. Furthermore, mRNA expression of interleukin-1b in adipose tissue and serum levels of nonesterified fatty acids in mice administered L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 20 publications
4
21
0
Order By: Relevance
“…Gut microbiota affects the muscular energy utilization preference (7) and metabolites (26) via the gut muscle axis. Previous studies showed that mice administered L. plantarum could regulate blood glucose levels in response to insulin (21) and prevent metabolic disturbances induced by a high-fructose diet (25). Our results suggest that L. plantarum TWK10 probiotics are beneficial to energy harvesting possibly due to glycogenesis regulation for exercise demand (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…Gut microbiota affects the muscular energy utilization preference (7) and metabolites (26) via the gut muscle axis. Previous studies showed that mice administered L. plantarum could regulate blood glucose levels in response to insulin (21) and prevent metabolic disturbances induced by a high-fructose diet (25). Our results suggest that L. plantarum TWK10 probiotics are beneficial to energy harvesting possibly due to glycogenesis regulation for exercise demand (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…Although the blood glucose concentrations were not significantly reduced in KKAy mice treated with OLL2712, an observable trend toward reduced rates of elevation of blood glucose concentrations was noted in the OLL2712 group compared with the control group (P = 0.09, Table 2). In a previous report, however, we demonstrated that OLL2712 administration significantly reduced blood glucose concentrations after insulin treatment in a dietinduced obesity model (Sakai et al, 2013). Accordingly, it is also possible that the administration of OLL2712 may be effective in ameliorating hyperglycemia.…”
mentioning
confidence: 67%
“…These effects were associated with increased number of Bifidobacterium and Lactobacillus strains. In high-fat diet-induced obese mice and streptozotocin- or alloxan-induced diabetic rats, administration of L. plantarum , L. acidophilus , or L. casei resulted in reduction of body weight, hyperglycemia, epididymal fat, triglyceride, insulin and leptin, lipase activity, non-esterified fatty acids, triglyceride, low density lipoprotein (LDL)-cholesterol, LDL/HDL (high density lipoprotein) ratio, and adipocyte interleukin-1beta mRNA expression [4043]. Supplementation with this probiotic also increased HDL-cholesterol, improved immunological parameters and exerted protective effects on the pancreas, liver and kidney.…”
Section: Modulation Of Gut Microbiota In the Management Of Metabolic mentioning
confidence: 99%